The Effectiveness of E-commerce Platforms Banyuwangimall.com in The Development of Small and Medium Enterprises - Muhammad Levia Dava Rezeki Effendi; Puji Susilo Asih; Iradhat Taqwa Sihidi; Ali Roziqin (Jurnal Administrasi Publik (Public Administration Journal), 2022)
This article aims to explain the effectiveness of e-commerce platforms Banyuwangimall.com in the development of Small and Medium Enterprises in Banyuwangi. The problem is focused on the problem of dysfunction on e-commerce platforms Banyuwangi-Mall.com as a place to buy and sell people online as well as to increase market share and competitiveness of small and medium-sized businesses.Â  To approach this problem, the reference indicators of effectiveness are used according to Budiani (2017), data is collected through literature studies, where sources and data are obtained from journals, books, online news, or websites. This study concluded that the effectiveness of the e-commerce platform Banyuwangimall.com in the development of small and medium-sized businesses has not been fully effective. Of the four effectiveness indicator variables, three variables have been fulfilled, but their implementation is still not optimal enough, the three variables are the alignment of program goals, socialization, and program monitoring. One variable that has not been fulfilled is the achievement of the program objectives. The malfunction of Banyuwangi-mall.com from the end of February 2021 to the end of January 2022 signifies the stagnation of the implementation of a program.